The Influence of Feeding Combination Silkworm (Tubifex sp.) with Commercial Feed on Growth Performance of Catfish (Clarias sp.) - Agustina, Dewi; Mukti, Retno Cahya (Universitas Malikussaleh, 2021)
This study aims to determine the growth of catfish (Clarias sp.) Seeds by giving a combination of silkworms (Tubifex sp.) and commercial feed. This research was conducted in August - October 2020 in the fish farming group of PT ASABRI, West Ilir II Palembang, South Sumatera. The treatments used in this study were 100% silkworm (control) feeding and a combination of feed treatment consisting of 75% commercial feed and 25% silkworms. Parameters include absolute weight growth, absolute length growth, feed efficiency, survival, and water quality. The results obtained from this study indicate that combination feeding (P1) obtained better results than the control (P0) with absolute weight growth data of 8.38 g, absolute length 7.39 cm, feed efficiency 56.38% and survival 87.50%.Keywords: catfish, commercial feed, combination, growth silkworm